Pengembangan Potensi Usaha Abon untuk Meningkatkan Daya Saing Produk di UMKM Ksatria Kelurahan Jagalan, Kecamatan Jebres, Surakarta - Adi Magna Patriadi Nuhriawangsa; Lilik Retna Kartikasari; Agung Budiharjo; Winny Swastike; Bayu Setya Hertanto (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Competitiveness in the competitiveness of Micro, Small and Medium Enterprises (MSMEs) is very important to be improved. This is because MSMEs are a force in driving economic development. The purpose of this activity is to improve the competitiveness of MSMEs products Ksatria Jagalan Village, Jebres Sub-district, Surakarta. The methods used are training and mentoring. The results achieved were an increase in the understanding of MSME, actors about marketing which includes aspects: MSME products including quality of product of abon, packaging of abon and labeling related to important information to be conveyed to consumers to increase the skills and existence of MSME. In addition, the factors of promotion of digital marketing era, price, technology-based marketing, branding, innovation and creativity, product competitiveness. The program's achievements are quite satisfactory. This can be seen from the achievements that have been obtained. The improvements made in this activity have made partners produce competitive products. The suggestion for this activity is that mentoring can be carried out continuously under mentoring and evaluation can be carried out periodically.